Electricity market design for a decarbonised future: An integrated approach - Peng, D; Poudineh, R (Oxford Institute for Energy Studies, 2017)
In recent years, the debate on electricity market design in the EU has focused on the fitness-for-purpose of the existing dominant design, the appropriateness of energy policy that underpins the existing market design, and on the process through which energy policy is coordinated with market design. In this paper, we contribute to this debate on all three levels. First, we propose a ‘module-and-level’-based framework to illustrate our diagnosis of coordination issues present in the EU’s power markets. We apply this framework to make a systematic identification of existing misalignments between the components of current market design and physical RES integration/financial RES support schemes. Secondly, we argue that the role of energy policy is not just in managing existing trade-offs between competitiveness, sustainability, and reliability, but also in encouraging innovations that increase the compatibility of energy policy objectives in the future. Finally, we propose a seven-step condition-dependent evolution of power market design, where the government/regulatory authority plays the role of meta-coordinator, matching the adaptation of market-based coordination modules with a hybrid future where distributed energy resources coexist with centralised generation, while decentralised market participants trade with each other and with incumbents.